THE ROLE OF BORROWINGS IN THE DEVELOPMENT OF LEXICAL DOUBLETS IN THE ENGLISH LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article the author provides information on the origin of lexical doublets together with the analysis of significance of borrowed words in the development of them. Furthermore, the reasons for borrowings are discussed in the article as well as examples or borrowed doublets which came into English from other languages.